2021 IEEE Power &Amp; Energy Society General Meeting (PESGM) 2021
DOI: 10.1109/pesgm46819.2021.9638108
|View full text |Cite
|
Sign up to set email alerts
|

Calculate Center-of-Inertia Frequency and System RoCoF Using PMU Data

Abstract: The power system frequency is important for the system overall stability. However, there does not exist a single measurement point of the system frequency due to the distributed nature of the system inertia and the small inconsistency of different generator rotors' electrical speeds in one synchronized system. This paper proposed a new approach to calculate the system center-of-inertia (COI) frequency and the rate-of-changeof-frequency (RoCoF) more accurately using PMU data at multiple locations. The COI frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Energies 2023, 16, x FOR PEER REVIEW 15 of points, we can obtain the approximate estimated value of the CoI frequency, so that t CoI RoCoF can be obtained, accordingly. Reference [100] proposes that the CoI frequen and RoCoF of the power system can be calculated more accurately by PMU data fro multiple locations. Firstly, the equivalent inertia constant is obtained by the least squar method, and then the CoI frequency is calculated according to Equation ( 4), and t RoCoF is the first-time derivative of CoI frequency; the simulation results show that t error can be effectively reduced.…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energies 2023, 16, x FOR PEER REVIEW 15 of points, we can obtain the approximate estimated value of the CoI frequency, so that t CoI RoCoF can be obtained, accordingly. Reference [100] proposes that the CoI frequen and RoCoF of the power system can be calculated more accurately by PMU data fro multiple locations. Firstly, the equivalent inertia constant is obtained by the least squar method, and then the CoI frequency is calculated according to Equation ( 4), and t RoCoF is the first-time derivative of CoI frequency; the simulation results show that t error can be effectively reduced.…”
Section: Other Methodsmentioning
confidence: 99%
“…Equation (8) implies that the measurement device that can track the dynamic voltage/current phase at a node of the power system, namely the synchrophasor, can be used to track the real-time local RoCoF with a proper algorithm; however, RoCoF estimation techniques face great challenges in accuracy and robustness. This section provides a comprehensive review of the existing real-time RoCoF tracking algorithms of synchrophasors, which can be divided into three main categories: (i) DFTbased [64][65][66][67][68][69][70][71][72][73][74][75][76], (ii) Kalman filter techniques [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92], and (iii) other methods [93][94][95][96][97][98][99][100]. The details for each category are provided in the subsection.…”
Section: Real-time Rocof Tracking Techniquesmentioning
confidence: 99%
“…For every system load level involved and every inertia reduction scenario, the single outage of generators and the step increase of loads (one at a time) were considered as sudden power imbalances. In this manner, an average frequency of the system was determined after the disturbance based on the following equation, where fCOI represents the frequency of the center of inertia [18] of the grid under study:…”
Section: A Dataset For the Studiesmentioning
confidence: 99%
“…One of the critical challenges in power systems operation planning with high penetration of inverter-based resources (IBRs) is the decrease in system inertia, which results in a high initial rate of change of frequency (ROCOF) [1]. Furthermore, recent theoretical studies [2], [3], [4] and datadriven analyzes [5], [6], [7] have shown that inertia providers are unevenly distributed across the system, and the frequency response after a disturbance has spatial-temporal characteristics. The practical problem is the unexpected tripping of The associate editor coordinating the review of this manuscript and approving it for publication was Youngjin Kim .…”
Section: Introduction a Motivationmentioning
confidence: 99%